Pathogenicity of Shiga Toxin Type 2e Escherichia coli in Pig Colibacillosis - Baldo, Valentina; Salogni, Cristian; Giovannini, Stefano; D'Incau, Mario; Boniotti, Maria Beatrice; Birbes, Laura; Pitozzi, Alessandra; Formenti, Nicoletta; Grassi, Andrea; Pasquali, Paolo; Alborali, Giovanni Loris (Frontiers in Veterinary Science, 2020)
Shiga toxin type 2e (Stx2e) Escherichia coli is the causative factor of diarrhea and edema in swine. The aims of this study were to determine the prevalence of Stx2e-producing E. coli isolates and to characterize isolates from clinical cases of pig colibacillosis and healthy swine. During the 11 years of the study (2006 – 2017), a total of 233 Stx2e-producing isolates were detected – 230 out of 2060 (11.16%) E. coli isolated from diseased pigs and 3 out of 171 (1.75%) from healthy swine. Stx2e-producing isolates were indeed more present in clinical colibacillosis cases than in healthy pigs (p = 0.0002). The predominant serogroup was O139 (79.82%) and the most common fimbrial factor present in these isolates was F18 (177 isolates), followed by F6 (5 isolates). The enterotoxins LTI, STa, and STb were detected in 10.43%, 41.73%, and 48.26% of the isolates, respectively. The predominant virotypes F18-Stx2e and F18-STa-STb-Stx2e were similarly present in weaners (33.33% and 35.52%) and finishers (38.30% and 25.53%). Among isolates from diseased pigs, O139 and F18 were the more frequently identified serogroup and virulence factor, respectively. Of the tested 230 Stx2e-producing isolates isolated from diseased pigs, 29 (12.60%) harboured genes encoding ESBL, particularly TEM (79.30%), CTX-M1 (17.20%), and CMY-2 (3.40%). Antimicrobial resistance to tetracycline was the most common characteristic (98.25%), followed by ampicillin (93.91%), cephalotin (90.43%) and trimethoprim/sulfamethoxazole (82.17%). Our results showed that Stx2e-producing E. coli were more frequently associated with clinical forms of colibacillosis, with minimal probability to isolate these isolates from healthy pigs.